Effects of interfacial interactions and of crystallization on rigid amorphous fraction and molecular dynamics in polylactide/silica nanocomposites: A methodological approach. (10th March 2017) - Klonos, Panagiotis; Pissis, Polycarpos
Abstract: We employ a partly new experimental approach to polymer nanocomposites (PNCs) based on a semicrystalline matrix, in order to distinguish between phenomena affiliated, on the one hand, to interactions between polymer and nanoparticles, and, on the other hand, to polymer crystals. Thus, effects of silica nanoparticles and of crystalline fraction ( CF ) on glass transition and segmental dynamics in poly (l –lactic acid) were investigated by means of differential scanning calorimetry (DSC) and broadband dielectric relaxation spectroscopy (DRS). Analysis of results involves combination of measurements on initially amorphous and on semicrystalline (annealed) samples. No change in the glass transition temperature by the filler is observed by DSC, whereas the heat capacity step decreases in the PNCs. The segmental α relaxation (dynamic glass transition) in DRS becomes, however, faster and weaker in the PNCs. Results are rationalized in terms of the rigid amorphous fraction ( RAF ) due to filler (interfacial polymer, RAF filler ) and due to polymer crystals ( RAF crystal ). RAF filler and RAF crystal were disentangled from the total RAF via two assumptions: (a) assuming the same RAF crystal to CF ratio in the neat matrix and the PNCs, and (b) assuming the same RAF filler in amorphous and semicrystalline samples. Changes of the various polymer fractions with composition show similar trends in DSC and DRS. RAF filler was found to increase with filler fraction, with a saturation for the largest loading (20 wt%), assigned to filler aggregation confirmed by morphological characterization. Both RAF crystal and mobile amorphous fraction, MAF, were found within experimental error almost constant with filler loading. The overall results suggest that interfacial interactions ( RAF filler ) in combination with changes in semicrystalline morphology dominate polymer dynamics in semicrystalline PNCs. Graphical abstract: Highlights: Heat capacity step and dielectric strength of α relaxation decrease in PLA PNCs. Separation of RAF due to filler, RAF filler, and to crystals, RAF crystal, under assumptions. Similar trends of RAF and MAF by DSC and DRS. Interfacial layer thickness for PLLA PNCs estimated in the range from 2 to 5 nm. Semicrystalline morphology explains effects on segmental dynamics and T g .